2018
DOI: 10.1021/acs.iecr.8b00451
|View full text |Cite
|
Sign up to set email alerts
|

Monomer Structure and Solvent Effects on Copolymer Composition in (Meth)acrylate Radical Copolymerization

Abstract: Solvent effects on reactivity ratios (ri ) and overall composition-averaged copolymer propagation rate coefficients (k p,cop) are generally not observed during methacrylic ester radical copolymerization. However, hydroxyl-bearing comonomers, such as 2-hydroxyethyl methacrylate (HEMA), lead to significant deviations from expectation for both ri and k p,cop, an effect that is highly dependent on solvent choice and rooted in hydrogen bond interactions. The current understanding of the influence of hydrogen bondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 73 publications
(193 reference statements)
0
21
0
Order By: Relevance
“…In line with previous studies, the polar HEMA has higher incorporation into the copolymer than the non-polar BMA. While this enhanced reactivity is explained by H-bonding between HEMA molecules, it is somewhat surprising, as discussed by Rooney and Hutchinson [18], that HEMA does not also enhance BMA reactivity to the same extent through H-bonding with the BMA carbonyl group; previous work has shown that BUOH as a solvent enhances BMA reactivity both during homopolymerization [12] and when copolymerized with styrene [15]. The result suggests that the intermolecular bonding between HEMA units is stronger than that between HEMA and BMA.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In line with previous studies, the polar HEMA has higher incorporation into the copolymer than the non-polar BMA. While this enhanced reactivity is explained by H-bonding between HEMA molecules, it is somewhat surprising, as discussed by Rooney and Hutchinson [18], that HEMA does not also enhance BMA reactivity to the same extent through H-bonding with the BMA carbonyl group; previous work has shown that BUOH as a solvent enhances BMA reactivity both during homopolymerization [12] and when copolymerized with styrene [15]. The result suggests that the intermolecular bonding between HEMA units is stronger than that between HEMA and BMA.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, it was concluded that the bootstrap effect alone cannot explain the magnitude of the increased HEMA incorporation. Rooney and Hutchinson [18] propose that the increased reactivity of HEMA results not from monomer aggregation, but rather from HEMA hydrogen bonding between monomer and a HEMA unit located on the growing chain close to the radical end in the non-polar solvent, increasing the incorporation rate of the HEMA into the copolymer relative to the bulk system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations